PENGARUH PERSEPSI KONSUMEN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA MOBIL MITSUBISHI DI PT. DIPO SUMBAR - Maria Herlin; Febsri Susanti (LP2M Universitas Bina Bangsa, 2024)
Globalization has had a huge impact on various industries, and other business fields are no exception in the automotive sector, which is increasingly present and competing in the midst of growth and the economy as well as changes in the flow of technology and the flow of information that is increasingly rapid. Companies compete fiercely to produce products with good quality, because it is very influential on consumer purchasing decisions. Various ways can be taken by companies in improving consumer purchasing decisions, including in paying attention to product quality and consumer perceptions, because these two variables greatly affect the purchasing decisions of each consumer. The purpose of this study is to determine the effect of consumer perceptions and product quality on purchasing decisions, based on the results of tests that have been carried out it can be seen 1. Consumer perceptions have a t-value greater than the t-table value, this can mean that the price has a positive effect and on consumer purchasing decisions on the purchase of Mitsubishi cars at PT DIPO Sumbar. 2. Product quality has a t-value greater than the t-table value; this means that product quality has a positive and significant influence on consumer purchasing decisions on the purchase of Mitsubishi cars at PT DIPO Sumbar